Molecular diagnosis of Smith-Magenis syndrome using MLPA (Multiplex Ligationdependent Probe Amplification) - Talavera Vargas-Machuca, Sergio (2017)
Medical genetics is rapidly advancing thanks to technologies that accurately define which genes are involved in the development of diseases. Some syndromes occur in the general population, and their diagnosis and treatment are important to provide patients with an adequate care and prognosis. We present the case of a dysmorphic child who was born at 33 weeks of pregnancy by caesarean delivery due to preeclampsia. Cytogenetic analysis showed a heterozygous deletion on the short arm of chromosome 17 (46, XX, del 17p11.2). The diagnosis was complemented by MLPA analysis, which measures the presence/absence of certain genes defined in some syndromes, and confirmed the deletion of 2.1 megabases of DNA, including the RAI1 gene, responsible for the Smith-Magenis syndrome.